1987
DOI: 10.1055/s-2007-1011779
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Beta-Endorphin in Response to Oral Glucose Tolerance Test in Obese Patients

Abstract: In order to clarify the possible interaction between endogenous opioids and glucose homeostasis in obesity we studied Beta-Endorphin (B-Ep), ACTH, cortisol and insulin plasma levels in response to an oral glucose tolerance test (OGTT) in 8 females suffering from uncomplicated obesity and in 6 healthy volunteers of normal weight. Results were evaluated in terms of secretion areas subtracted from basal value. Basal glucose, insulin and B-Ep levels were significantly higher in the obese patients compared to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…According to Getto, Fullerton and Carlson (1984), whose results have been recently confirmed by Squadrito, Cucinotta, Arcoraci, Sturniolo, Arcoraci, Morabito, Corica, Caputi and Squadrito (1989), glucose produces an increase in plasma beta-endorphin levels in both lean and obese subjects, although the response of obese subjects is usually delayed and increased. In contrast, Scavo, Facchinetti, Barletta, Petraglia, Buzzetti, Monaco, Giovannini and Genazzani (1987) found significant increases of plasma beta-endorphin concentrations after oral glucose in obese but not in normal-weight controls, whereas Vettor, Martini, Manno, Cestaro, Federspil and Sicolo (1985), while confirming the presence of hyperendorphinemia in the basal state, were unable to find an increase in plasma beta-endorphin concentrations after the ingestion of a carbohydrate-rich meal in obese subjects. Although the lack of beta-endorphin response to intravenous glucose challenge in obesity seems to speak in favour of a gut-derived beta-endorphin source, at the present the data are still discordant and the question remains open.…”
Section: Opioid Peptides and Food Intakementioning
confidence: 82%
“…According to Getto, Fullerton and Carlson (1984), whose results have been recently confirmed by Squadrito, Cucinotta, Arcoraci, Sturniolo, Arcoraci, Morabito, Corica, Caputi and Squadrito (1989), glucose produces an increase in plasma beta-endorphin levels in both lean and obese subjects, although the response of obese subjects is usually delayed and increased. In contrast, Scavo, Facchinetti, Barletta, Petraglia, Buzzetti, Monaco, Giovannini and Genazzani (1987) found significant increases of plasma beta-endorphin concentrations after oral glucose in obese but not in normal-weight controls, whereas Vettor, Martini, Manno, Cestaro, Federspil and Sicolo (1985), while confirming the presence of hyperendorphinemia in the basal state, were unable to find an increase in plasma beta-endorphin concentrations after the ingestion of a carbohydrate-rich meal in obese subjects. Although the lack of beta-endorphin response to intravenous glucose challenge in obesity seems to speak in favour of a gut-derived beta-endorphin source, at the present the data are still discordant and the question remains open.…”
Section: Opioid Peptides and Food Intakementioning
confidence: 82%
“…This has been demonstrated in the case of pancreatic polypeptide and enteroglucagon of which the responses to meals were lower in obese subjects [16], The finding that a decrease in P-endorphin levels occurred only after the CHO meal (600 kcal), suggests an influence by macronutrients in the setting of a regular meal. It has been reported that oral administration of glucose only (about 300 kcal) induces no response [12] or even a rise [10] in plasma P-endorphin in normal-weight controls and an increase in P-endorphin levels in obese subjects [10. 12.…”
Section: Discussionmentioning
confidence: 99%
“…there is evidence that P-endorphin is also produced in the pancreatic islets [5], suggesting a role for P-endorphin in glucose regula tion. Lean and obese subjects have been reported to exhibit a different response to intravenous infusion of p-endorphin in pharmacological doses, suggesting an in creased responsiveness of P-cells to P-endorphin in hu man obesity [6][7][8][9], Oral or intravenous administration of glucose has been reported to cause an increase in plasma P-endorphin which is greater in obese subjects than in controls [10][11][12],…”
mentioning
confidence: 99%
“…Opioid receptors have been demonstrated in both the islets of Langerhans and the liver (63). In response to oral or IV glucose administration, obese patients have greater secretion of both insulin and &endorphin than normal weight controls (40,102). &endorphin causes a rapid fxst phase increase in insulin secretion but no change in the second phase response despite continuous B-endorphin infusion (16).…”
Section: Endogenous Opioidsmentioning
confidence: 99%